Financial Literacy And Social Capital On Performance For Msme Sustainability - Wawan Ruswandi; Rosanna Wulandari; Eris Juliansyah; Dewi Resmanasari; Virgy Putri Mulia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research design is explanatory and aims to understand various dimensions of MSME performance, MSME sustainability financial literacy, and social capital followed by a conclusive approach where this method aims to outline and clarify the predictive statements formulated. Primary data with an open questionnaire instrument is a data collection method. Analysis of the problem formulation was carried out in several stages using Path Analysis. The research sample consisted of 92 MSME actors from a population of 1,100 verified MSME actors in Sukabumi City. These findings indicate that: 1)Financial literacy has a tremendous impact on the performance of MSMEs. 2) Social Capital has a tremendous impact on MSME performance. 3)Financial literacy has a tremendous impact on the sustainability of MSMEs. 4)Social Capital has a tremendous impact on the sustainability of MSMEs. 5) The performance of MSMEs has a tremendous impact on the sustainability of MSMEs. 6)Financial literacy has a tremendous impact on the sustainability of MSMEs through MSME performance and 7).Social capital has a tremendous impact on the sustainability of MSMEs through MSME performance.